Delirio posoperatorio en pacientes geriátricos sometidos a Anestesia General versus Neuroaxial, en dos hospitales de Quito - Ecuador: Postoperative delirium in geriatric patients subjected to general anesthesia, compared to those subjected to neuraxial anesthesia, in two hospitals of the city of Quito (La U Investiga, 2020)
Objective: To determine the prevalence of POD in patients from the age of 65 and over, 72 hours after undergoing surgery under general or neuraxial anesthesia. The assessment will be conducted using the Confusion Assessment Method (CAM) in two hospitals of the city of Quito. Methodology: This study had an epidemiological, observational, cross-sectional and analytical design that included 162 elderly patientsthat met the study’s inclusion criteria. The data was collected throughout the period between August and September 2016. Results: The overall prevalence of POD in this study was 36.4% (n=59). General anesthesia was associated with an increased risk of delirium compared to neuraxial, the analysis found an adjusted OR of: 4.07 (95% CI: 1.89 - 9.33). In the multivariate analysis, the transfusion of blood components was strongly associated with the development of postoperative delirium, with an OR adj: 0.65 (95% CI: 0.24 - 1.64; p = 0.37). Interpretation: General anesthesia and transfusion of blood products were identified as independent risk factors for the development of postoperative delirium. Conclusions: Geriatric patients undergoing general anesthesia have four times the risk of triggering postoperative delirium than those undergoing surgery under neuraxial anesthesia. Blood transfusion is an independent risk factor for postoperative delirium.
Keywords: Delirium; general anesthesia; neuraxial anesthesia; Confusion Assessment Method; older adult